2004
DOI: 10.1111/j.1365-2929.2004.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis can be a useful standard setting tool in a high stakes OSCE assessment

Abstract: Factor analysis is a useful tool for characterising and quantifying the skills that are assessed in an OSCE. Standard setting procedures can be used to calculate cut-off scores for each underlying factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 5 publications
0
29
0
3
Order By: Relevance
“…Twenty five studies reported the duration of CS stations, with the shortest being 5 min long and the longest being 20 min long [11,, whilst almost half of the reviewed papers ranged from 5 to 8 min [11,24,[26][27][28][29][30][31]33,[36][37][38][39][42][43][44]. Four studies reported short and long case scenarios with obviously different durations [11,31,32,37], in contrast to nine studies which did not report station length at all [15,[47][48][49][50][51][52][53][54][55].…”
Section: Content Analysismentioning
confidence: 95%
“…Twenty five studies reported the duration of CS stations, with the shortest being 5 min long and the longest being 20 min long [11,, whilst almost half of the reviewed papers ranged from 5 to 8 min [11,24,[26][27][28][29][30][31]33,[36][37][38][39][42][43][44]. Four studies reported short and long case scenarios with obviously different durations [11,31,32,37], in contrast to nine studies which did not report station length at all [15,[47][48][49][50][51][52][53][54][55].…”
Section: Content Analysismentioning
confidence: 95%
“…Entre los instrumentos de medida de la fiabilidad o consistencia interna de la prueba ECOE, el más utilizado es el alfa de Cronbach 26 . La fiabilidad global de la prueba en el presente trabajo es de 0,79, lo que ha de considerarse como un valor satisfactorio al compararlo con estudios similares existentes 10,17 .…”
Section: Discussionunclassified
“…Table 1 show the frequency of appearance of the stations where at least once a yellow card is dealt. compensatory or an additional rating, addressing behavior and overall impression of competence, is advisable for the final pass-fail decision [13].…”
Section: Resultsmentioning
confidence: 99%
“…There are sufficient cases reporting on contradictory results between OSCE-and residency or internshipperformance [13]. Therefore the question imposes whether a considered as subject of an exploratory study.…”
Section: Introductionmentioning
confidence: 99%